Pengaruh Perkuliahan dengan Metode dalam Jaringan (Daring) terhadap Minat Belajar Mahasiswa (Studi Kasus pada Program Studi Teknologi Pangan Universitas Islam Indragiri) - Mardesci, Hermiza; Mardesci, Afrina (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2020)
This study aims to determine the effect of lectures with online methods on student learning interest. The sample used in this study were students from the Food Technology of Indragiri Islamic University. Data collection was carried out in this study through observation, literature review, and questionnaire distribution. The instruments in this study include the independent variable (X) which is the Online Course Method, and the dependent variable (Y) is the Student Learning Interest. Instrument testing is done by normality test (Pearson Product Moment correlation), and reliability test (Cronbach Alpha coefficient). Data analysis was performed with simple linear regression, and to see the strength of the relationship between the two variables used the Spearman Rank correlation test. The results of this study indicate that lectures with the Online Course Method have an influence on student interest in learning. However, the effect here shows a negative relationship between the two variables. This can be seen from the negative regression coefficient. It can be concluded that if online lectures increase, students' interest in learning decreases.